Classificação de desfechos clínicos em 30 dias reportados por investigadores ou realizada por meio de um comitê de revisores independente em pacientes com síndrome coronariana aguda incluídos no estudo randomizado SECURE-PCI - Laranjeira, Ligia Nasi [UNIFESP] (2019)
Objective: Using data from the SECURE-PCI trial, which included patients with acute coronary syndrome randomized to two loading doses (before and 24 hours after a planned percutaneous coronary intervention) of atorvastatin or placebo, this study aims to: describe the organization and methodology of the clinical events classification process performed in this study; to compare the clinical outcome rates derived from two forms of outcome identification: 1-defined by the clinical events classification committee 2-outcomes reported directly by the site investigators and describe the treatment effect of the atorvastatin doses or placebo on outcomes validated by an independent clinical event classification committee or reported directly by investigators. Methods: This study evaluates the SECURE-PCI outcomes reported directly by the sites investigators in the study case report form. SECURE-PCI was a multicenter, national, pragmatic, double-blind, with intention-to-treat analysis, randomized controlled trial. The primary objective is to determine if administration of loading doses of atorvastatin reduced the rate of major cardiovascular events in 30 days in patients with acute coronary syndrome undergoing a planned percutaneous coronary intervention. The study investigator filled out the case reported forms with information regarding outcomes or possible outcomes and this information was validated by a clinical event classification committee. Results: The SECURE-PCI clinical event classification process includes the following steps: identifying suspected events, evaluating event-related source documents by at least two independent physician reviewers, and determining the final event classification. From 4191 patients included in the trial, the site investigators reported 249 patients with major cardiovascular events. 38 (15.26%) of these were not validated by the event classification committee; on the other hand, the investigators did not report major cardiovascular events in 68 (24.37%) patients, which were validated by the clinical event classification committee. The treatment effect of the SECURE-PCI study considering the rate of combined outcomes validated by the clinical event classification committee versus the combined outcome rate reported directly by the investigators results in Hazard ratio = 0.88, 95% CI (69, 1.11), p = 0.27 versus Hazard ratio = 1.03, 95% CI (0.80, 1.32), p = 0.82. Considering the group of patients who underwent percutaneous coronary intervention, the treatment effect of the combined outcome that was validated by the clinical events classification versus that reported by the investigators was Hazard ratio = 0.72, 95% CI (0.54; 0.96), p = 0.02) versus Hazard ratio = 0.85, 95% CI (0.63, 1.17), p = 0.32. Conclusions: Considering all the combined events reported by the investigators, 84.8% were confirmed by the clinical events classification committee however, the investigators did not report major cardiovascular events in 68 (24,37%) patients, which were identified by the clinical event classification committee. The outcomes with highest difference between those reported by the investigators and those validated by the clinical events classification were periprocedure myocardial infarction and non-planned revascularization. In general results from the SECURE-PCI were similar considering data classified by an independent clinical event classification committee or reported by investigators. However, in the pre-specified subgroup analysis of patients who underwent percutaneous coronary intervention, the results were different: when outcomes reported directly by the investigators were analyzed, we did not find significant differences between the patients who received loading doses of statin and the control group. On the other hand, when using clinical events classification results, we demonstrated that the use of loading doses of statin reduced major cardiovascular events in this subgroup of patients.